2008
DOI: 10.2147/ndt.s2827
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness analysis for trigeminal neuralgia: Cyberknife vs microvascular decompression

Abstract: Background/Aims: We present the preliminary results of a cost-effectiveness analysis of cyberknife radiosurgery (CKR) versus microvascular decompression (MVD) for patients with medically unresponsive trigeminal neuralgia. Methods: Direct healthcare costs from hospital's perspective attributable to CKR and MVD were collected. Pain level caused by trigeminal neuralgia was measured through the Barrow Neurological Institute pain intensity scoring criteria, at admission and after an average of 6 months follow-up. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 37 publications
(32 reference statements)
0
7
0
Order By: Relevance
“…In the population studied, both procedures were equally effective at six months, yet CyberKnife radiosurgery reduced hospital costs by an average of 34%. The robustness of this result was confirmed by sensitivity analysis [ 45 ]. In Germany, a study conducted by Bijlani et al investigated the cost-effectiveness of SRS compared to surgical resection for acoustic neuroma, meningioma, and arteriovenous malformations [ 46 , 47 ].…”
Section: Reviewmentioning
confidence: 56%
See 1 more Smart Citation
“…In the population studied, both procedures were equally effective at six months, yet CyberKnife radiosurgery reduced hospital costs by an average of 34%. The robustness of this result was confirmed by sensitivity analysis [ 45 ]. In Germany, a study conducted by Bijlani et al investigated the cost-effectiveness of SRS compared to surgical resection for acoustic neuroma, meningioma, and arteriovenous malformations [ 46 , 47 ].…”
Section: Reviewmentioning
confidence: 56%
“…From a cost-effectiveness standpoint, a significant benefit of utilizing stereotactic radiosurgery (SRS) to treat patients is that it enables is that SRS can be performed in an outpatient setting, thereby avoiding excessive costs associated with hospital admissions. A recent economic study performed a cost-effective analysis for using CyberKnife SRS to treat trigeminal neuralgia [ 45 ]. The two main therapeutic options compared in the report used to treat trigeminal neuralgia were microvascular decompression and SRS.…”
Section: Reviewmentioning
confidence: 99%
“…Only a few studies have evaluated the effects of drugs in the reduction of costs in TN, 34 or have compared the cost of different TN surgical protocols. 32 , 33 In accordance with a less expensive experience resulting from MVD surgery, in a comparison between this surgery, glycerol rhizotomy, and stereotactic radiosurgery, it was shown that in longer follow-up intervals MVD is predicted to be the most cost-effective surgery and should be considered the preferred operation for patients. 32 However, recent data point to cyberknife radiosurgery being a cost-saving alternative to MVD.…”
Section: Discussionmentioning
confidence: 89%
“… 32 However, recent data point to cyberknife radiosurgery being a cost-saving alternative to MVD. 33 The only study showing cost-saving using drug therapy in TN point to the use of pregabalin. 34 Finally, to the best of our knowledge, the present paper is the first attempt to compare clinical outcomes and costs among pharmacological protocols and the most common surgical approach in TN (excluding radiosurgery centers).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation